Robinson's paradigms and exercises in Syriac grammar - Coakley, J.F. (Oxford University Press, 2002)
T. H. Robinson published Paradigms and Exercises in Syriac Grammar in 1915 to meet the need for 'something of an elementary nature which should be of value to the student who takes up Syriac for the first time'. Since then, the book has met this need for generations of students. Still, teachers have recognized its weaknesses and this fifth edition is a thorough revision. Much of the old explanatory text and many of the exercises have been superseded. Some matters of grammar and pronunciation receive more systematic treatment and there are new appendices to introduce the estrangela and East Syriac scripts. In its format and level, however, the book aims to be, as before, an approachable introduction to this important language